Retrieval of a Displaced Right Mandibular Third Molar Root Fragment from the Submandibular Space: A Case Report - Sittichai, Sittisak (Journal of Health Science of Thailand, 2018)
A case of a displaced right mandibular third molar root fragment into the submandibular space is presented in this report. A 24 year-old single Thai woman was referred from a private dental clinic because a root of the right mandibular third molar was fractured and displaced into the lingual area while being removed about 2 hours previously. The patient presented with clinical features of the remaining empty socket of the right mandibular third molar being extracted, lingual cortical plate was destroyed at bleeding area . Radiographic examination showed the fracture root was under the socket at the same level of the inferior alveolar canal. The patient was treated by flap operation to remove the root fragment under local anesthesia. The ulceration healed well after treatment. In addition, the causes of the root fracture while being extraction and the fractured root was displaced into adjacent structures were reviewed in order to prevent complications.